Jute/Hemp bio-epoxy hybrid bio-composites: Influence of stacking sequence on adhesion of fiber-matrix. (March 2022) - Vinod, A.; Tengsuthiwat, Jiratti; Gowda, Yashas; Vijay, R.; Sanjay, M.R.; Siengchin, Suchart; Dhakal, Hom Nath
Abstract: In the current research, four different sequential laminates of Jute (J) and Hemp (H) fibers reinforced hybrid bio-epoxy composites were developed by using the hand lay-up method. The effect of the layering sequence of laminates was evaluated through mechanical properties such as tensile, flexural, interlaminar shear, and impact tests, and physical properties like water absorption, percentage void, and density. The stacking sequence showed minor changes in the hardness of the composites, while the mechanical performance of the hybrid laminates was comparable to the pure hemp laminate. The hybrid composite hemp/jute/hemp showed the highest tensile strength of 65.44 MPa, and a similar trend was observed in flexural results. The mechanical test results revealed that hybridization with hemp fiber as a skin layer and jute fiber as a core layer can improve the tensile and flexural strength, but it will decrease interlaminar shear strength. Thermal stability and fracture morphology are analyzed using thermogravimetric analysis and scanning electron microscopic images.